Evaluation of a live, attenuated recombinant influenza vaccine in high school children. - Schiff, G M (1975)
A live, attenuated, recombinant influenza vaccine (Alice strain) administered intranasally was evaluated in high school students and compared with intranasal placebo and subcutaneous, inactivated, bivalent influenza vaccine. The Alice strain was antigenic, increasing the geometric mean titer (GMT) from a prestudy level of 30.2 to a postvaccine level of 189.6. The inactivated vaccine increased the GMT from 32.9 to 361.8. There was no increase in the GMT among the placebo recipients. The Alice strain produced little reaction. With an antigenic, safe, acceptable, live, attenuated influenza vaccine available, immunization on a widespread basis should be considered.